Mid to long term outcomes of Laparoscopic Sleeve Gastrectomy in Indian population: 3–7 year results – A retrospective cohort study. (December 2017) - Garg, Harshit; Aggarwal, Sandeep; Misra, Mahesh Chandra; Priyadarshini, Pratyusha; Swami, Ashish; Kashyap, Lokesh; Jaiswal, Richa
Abstract: Introduction: Few studies have addressed the mid to long term impact of Laparoscopic Sleeve Gastrectomy (LSG) on weight loss and obesity associated co-morbidities, particularly in Indian population. The aim of this study is to assess the efficacy of LSG in morbid obesity over 3–7 years follow up. Materials and methods: Data of all patients who underwent LSG between January 2008 and March 2015 and completed their at least 1 year follow up till March 2016 was retrospectively reviewed using a prospectively collected database. Results: 424 patients undergoing primary LSG were included. The mean age (±2SD) was 39.8 ± 22.5 years and the mean Body Mass Index (BMI) (±2SD) was 46.67 ± 15.8 kg/m 2 . 124 patients (29.2%) were super-obese (BMI >50 kg/m 2 ). The percentage follow-up at 1 year, 3 years, 5 years and 7 years was 78.3%, 66.7%, 42.3% and 38.4% respectively. The mean percentage Excess weight Loss (%EWL) (±2SD) at 1year, 3years, 5years, and 7years was 71.8 (±50.5%), 64.95% (±41.8%), 61.7% (±46.2%) and 57.15% (±50.2%) respectively. The preoperative BMI significantly correlated with %EWL at 5 year (r 2  = 0.107, p = 0.018). The overall complication rate was 5.8%. Early complications included staple line leak (1.2%), bleeding (1.2%), deep venous thrombosis (0.4%) and 30-day mortality (0.21%). Late complications included stricture formation (0.21%) and new onset Gastro-esophageal Reflux Disease (GERD) (2.8%).At 5 years, 83.3% of diabetic patients showed remission while rest showed improvement in glycemic control with decrease in dosage. 69.3% patients showed improvement in hypertension, 100% patients showed improvement in Obstructive Sleep Apnea Syndrome, 75% patients showed improvement in hypothyroidism after surgery. GERD resolved in 62.8% patients while worsened in 11.4% patients. Conclusions: LSG has durable weight loss at 5 year with %EWL of 61% and significant resolution of obesity associated co-morbidities. Highlights: Few studies have addressed the mid and long-term results of LSG in Indian population. 424 patients undergoing LSG were assessed. 5 years after surgery, the mean percentage excess weight loss was 61.7 (± 46.2%) with a mean follow-up of 42.3%. There was significant improvement in obesity associated co-morbidities. LSG has durable weight loss and significant impact on comorbidities over 5 years follow-up.